ответ:
[tex]\displaystyle 1)-2x-10\\\\2)5m-10,7\\\\3)\frac{1}{3}a-\frac{13}{5}[/tex]
решение:
[tex]\displaystyle 1)7(x-3)+(11-9x)=7x-21+(11-9x)=7x-21+11-9x=-2x-21+11=2x-10\\\\2)2,4(5m-3)-3,5(2m+1)=12m-7,2-3,5(2m+1)=12m-7,2-7m-3,5=5m-7,2-3,5=5m-10,7\\\\3)\frac{8}{15}(5a+3)-(2\frac{1}{3}a+4\frac{1}{5})=\frac{8}{3}a+\frac{8}{5}-(2\frac{1}{3}a+4\frac{1}{5})=\frac{8}{3}a+\frac{8}{5}-(\frac{7}{3}a+4\frac{1}{5})=\\\\\frac{8}{3}a+\frac{8}{5}-(\frac{7}{3}a+\frac{21}{5})=\frac{8}{3}a+\frac{8}{5}-\frac{7}{3}a-\frac{21}{5}=\frac{1}{3}a+\frac{8}{5}-\frac{21}{5}=\frac{1}{3}a-\frac{13}{5}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
ответ:
[tex]\displaystyle 1)-2x-10\\\\2)5m-10,7\\\\3)\frac{1}{3}a-\frac{13}{5}[/tex]
решение:
[tex]\displaystyle 1)7(x-3)+(11-9x)=7x-21+(11-9x)=7x-21+11-9x=-2x-21+11=2x-10\\\\2)2,4(5m-3)-3,5(2m+1)=12m-7,2-3,5(2m+1)=12m-7,2-7m-3,5=5m-7,2-3,5=5m-10,7\\\\3)\frac{8}{15}(5a+3)-(2\frac{1}{3}a+4\frac{1}{5})=\frac{8}{3}a+\frac{8}{5}-(2\frac{1}{3}a+4\frac{1}{5})=\frac{8}{3}a+\frac{8}{5}-(\frac{7}{3}a+4\frac{1}{5})=\\\\\frac{8}{3}a+\frac{8}{5}-(\frac{7}{3}a+\frac{21}{5})=\frac{8}{3}a+\frac{8}{5}-\frac{7}{3}a-\frac{21}{5}=\frac{1}{3}a+\frac{8}{5}-\frac{21}{5}=\frac{1}{3}a-\frac{13}{5}[/tex]